2021
DOI: 10.26555/jiteki.v7i1.20420
|View full text |Cite
|
Sign up to set email alerts
|

Design of an Adaptive Super-Twisting Control for the Cart-Pole Inverted Pendulum System

Abstract: A cart-pole inverted pendulum system is one of the underactuated systems that has been used in many applications. This research aims to study the design and the effectiveness of the Adaptive Super-Twisting controller to stabilize the system by comparing it with other previous control methods. A stabilization control of the pendulum upright using the Adaptive Super-Twisting algorithm (ASTA), was investigated. The proposed controller was designed based on the decoupling algorithm method to solve the coupled cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The sliding mode control is a robust nonlinear controller which can easily handle a system's nonlinearity, uncertainty and model mismatch [49]- [52]. It has been implemented to control both linear and nonlinear systems: hydraulic [53][54], single machine infinite bus system [55], inverted pendulum [56]- [58], DC motor [59], induction motor [60], suspension [61], permanent magnet synchronous generator [62], hyperchaotic system [63], quadcopter [64], mobile robot [65][66], stepper motor [67], tank system [68] and robot manipulator [69]. According to study findings, SMC has been reported to give promising results.…”
Section: Introductionmentioning
confidence: 99%
“…The sliding mode control is a robust nonlinear controller which can easily handle a system's nonlinearity, uncertainty and model mismatch [49]- [52]. It has been implemented to control both linear and nonlinear systems: hydraulic [53][54], single machine infinite bus system [55], inverted pendulum [56]- [58], DC motor [59], induction motor [60], suspension [61], permanent magnet synchronous generator [62], hyperchaotic system [63], quadcopter [64], mobile robot [65][66], stepper motor [67], tank system [68] and robot manipulator [69]. According to study findings, SMC has been reported to give promising results.…”
Section: Introductionmentioning
confidence: 99%
“…The Inverted Pendulum is a highly nonlinear [1], unstable [2], fast dynamic [3], under-actuated system [4], [5], and multivariable system [6]. This system belongs to the under-actuated mechanical system, which its control inputs are more than its degrees of freedom [7], [6], [8], [9], [10]. This characteristic encouraged many researchers to use it as a traditional benchmark for the creation, testing, assessing, and comparing of different classical and contemporary control techniques [6].…”
Section: Introductionmentioning
confidence: 99%
“…An inverted pendulum has a center of gravity above the fulcrum [28]. The inverted pendulum's basic concept is to find and stabilize the stick's position above the robot [29]. This robot configuration design is similar to human feet.…”
mentioning
confidence: 99%